Knowledge attitudes and practice of some componests of reproductice health among yong female garment factory workers in the medical officer of health area Polgahawela - Srimanne, S.T.G (My University, 2006)
Information on this cross sectional descriptive study was gathered from 300 participants by using self administered questioner. Knowledge, attitudes and practices assessed on conception, sexually and contraception, STI and AIDSm abortion and sub fertility. Questionnaire was given to all participants during lunch. Half of the participants 52.2 percent could respond with correct answers to all questions. Knowledge on abortion was fairly good ( 64.5 percent) closely followed by knowledge on STI and AIDS. It was disappointing to find that knowledge on conception and sexually was very low with only 39.7 percent correct answers.